2013
DOI: 10.5694/mja12.10499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an electronic medical record information system on emergency department performance

Abstract: Implementation of the FirstNet electronic medical record system was associated with deterioration in ED KPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…Our study also does not focus on the ramp-up period of EHR implementation as several studies have already well highlighted the disruption caused by the ramp-up period immediately following EHR adoption. 21,22 Our results have face validity, showing a disruption in operational measures immediately after introduction of EHR technology (Figures 1 and 2); however, our study focuses on the long-term performance across a series of operational measures of performance. Second, not all operational measures were available and this study is not a comprehensive assessment of the effect of EHRs on clinical care and delivery.…”
Section: Limitationsmentioning
confidence: 69%
“…Our study also does not focus on the ramp-up period of EHR implementation as several studies have already well highlighted the disruption caused by the ramp-up period immediately following EHR adoption. 21,22 Our results have face validity, showing a disruption in operational measures immediately after introduction of EHR technology (Figures 1 and 2); however, our study focuses on the long-term performance across a series of operational measures of performance. Second, not all operational measures were available and this study is not a comprehensive assessment of the effect of EHRs on clinical care and delivery.…”
Section: Limitationsmentioning
confidence: 69%
“…Mohan, Bishop and Mallows [83] investigated the effects of EHR on time factors in the ED, and found significant increases in all (waiting time, treatment time and total time for patients who were eventually discharged). In addition, Park, Lee and Chen [84] found an increase in ED physicians' documentation times following a transition to working with an EHR.…”
Section: Ehr and Emergency Department Performancementioning
confidence: 95%
“…According to their study, they stated that we found a reduction in performance with respect to ED KPIs after implementation of the First Net system. So Implementation of the First Net electronic medical record system was associated with deterioration in ED KPIs [20].…”
Section: Resultsmentioning
confidence: 99%
“…Mohan et al in 2009 conducted a retrospective study to determine whether implementation of the Cerner First Net electronic medical record system was associated with any change in ED performance [20]. First Net (Cerner), an EMR system, has been introduced in emergency departments (EDs) around New South Wales since 2007.…”
Section: The Impact Of It On the Ed Through The Performance Indicatorsmentioning
confidence: 99%